Inovasi Perencanaan Anggaran Belanja Kegiatan Melalui Sistem Informasi Pemerintahan Daerah (SIPD) di Badan Kesatuan Bangsa dan Politik Kabupaten Sidoarjo - Ahmad Nurrafi’ Arfitsani; Ananta Prathama (Public Service and Governance Journal, 2025)
This study examines the implementation of the Regional Government Information System (SIPD) for budget planning of activity expenditures at Bakesbangpol Sidoarjo. SIPD, an integrated system, aims to enhance the effectiveness and efficiency of planning and budgeting in accordance with the Ministry of Home Affairs Regulation Number 70 of 2019. Using a qualitative approach with observations, interviews, and document studies, the research reveals that SIPD offers advantages such as data synchronization between central and local governments, despite challenges like limited human resources and technical server issues. The implementation of SIPD in Bakesbangpol Sidoarjo requires adaptation and capacity-building to optimize the system. This study concludes by emphasizing the importance of technology-based innovation management in achieving transparency and accountability in regional budget planning.